Grotescul geniului şi geniul grotesc - Alunița Cofan (Revista de Istorie și Teorie Literară)
The pages of this article contain a hermeneutical analysis of the grotesque into Eugen Ionescu’s biographical study Tragic and Grotesque Life of Victor Hugo. We have two points of view of grotesque here: the first one is a theoretical significance and the second one is an inside presence in narrative scenes. Deconstruction of logical methods, as well as syllogism, is pointing to the grotesque non-values: risible, clownish, horrible.